PENGARUH LATAR BELAKANG PENDIDIKAN PENGALAMAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA KANTOR BPBD KABUPATEN BOYOLALI - Pambuko, Indrayana Putro; Hegy Suryana, Alean Kistiani; Safitri, Unna Ria; Purwanto, Hari (Universitas Boyolali, 2024)
The purpose of this study was to assess (1) the effect of educational background on employee performance, (2) the effect of work experience on employee performance, (3) the effect of motivation on employee performance, and (4) the effect of educational background and work experience on employee performance .The causal research approach is taken in this study. The sample of this study were all employees of the Boyolali Regency BPBD office, totaling 54 people. The data comes from the results of employee questionnaires and is assessed using multiple linear regression analysis techniques.The research results obtained show that (1) educational background affects employee performance can be seen from p-value = 0.037 < a = 0.05 (2) work experience does not affect employee performance can be seen from p-value = 0.696 > a = 0.05 (3) motivation affects employee performance can be seen from p-value = 0.002 <0.05 (4) educational background and work experience affect employee performance can be seen from p-value = 0.000 < 0.05.